THE EFFECT OF STRESS ON PERSONALITY - Ilyasov Islam Yaxiya uli; Seytniyazova Alfiya Bekpolat qizi; Palvasheva Mubarek Xazilbekovna; Jiemuratova Sharigul Qutlimurat qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article presents the data of information about stress and its impact on personality.